The kinematic chain of arm elevation is impaired in patients with chronic obstructive pulmonary disease - Morais, Nuno (2020)
Patients with chronic obstructive pulmonary disease (COPD) often complain about difficulties in performing activities with their arms above shoulders height. These difficulties have been associated with increased cardiorespiratory demand and altered lung mechanics; however, musculoskeletal-related mechanisms may also contribute to constrain the mechanics of the upper body quadrant, increasing the effort to perform the activities. This exploratory research aimed to assess potential changes in the kinematic chain of arm elevation in patients with COPD. A secondary analysis from a cross-sectional exploratory case-control and prediction study was conducted in 15 patients with COPD (2 females) and 15 controls (8 females) matched for age and body mass index. The sagittal alignment and active range of motion (ROM) of the head, thoracic spine and shoulder complex were measured, using a computer software, in digital lateral photographs obtained in three different testing positions: arms at rest, arms at 90° of shoulder flexion and full arm elevation. From rest to full arm elevation, both groups moved from a more flexed to a less flexed or more upright thoracic spine position (∼7°, p < 0.001, 0.419 < ηp2 <0.767). However, the COPD group showed significantly less shoulder flexion (∼12°, p = 0.007, d = 1.05) and thoracic spine extension (∼6°, p = 0.015, ηp2 = 0.139) ROM than the control group in the full arm elevation position. These findings suggest that this population may show changes in the kinematic chain of arm elevation that possibly contribute to arm movement-related complains and limited performance in their daily living.